![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: y=x^tanx+sinx^cosx - y=e^x(sinx+cosx) - y=sinx^cosx find dy/dx - y sinx cosx - y=sinx cosx derivative - y=sinx+cosx graph - (1+cosx)y'=sinx(sinx+sinx cosx-y) - cos(x+y)=cosx cosy-sinx siny - (cosx+cosy)^2+(sinx-siny)^2=4cos^2x+y)/2 - cos(x+y)=cosx cosy-sinx siny proof - sinx-siny/cosx+cosy=tan x-y/2 - (cosx-cosy)^2+(sinx-siny)^2=4sin^2x-y/2) - y=tan^-1(cosx/1+sinx) - prove that sinx-siny/cosx+cosy=tan x-y/2 - y sinx cosx Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.